Critical policy Analysis - O'Sullivan, Dominic; Came, Heather (Encyclopedia of Health Research in the Social Sciences, 2023)
Critical policy analysis (CPA) is a technique concerned with how the location of power within the policy system influences social outcomes. CPA shows how and why it is unreasonable to assume that policy making is a politically neutral, objective, and simple technical process. This entry illustrates critical policy analysis through the example of colonial health policy in New Zealand. Institutional racism is often normalised within colonial settings and CPA can respond with a range of tools to privilege Indigenous values and contexts in policy development and implementation. Critical Tiriti Analysis is an emerging CPA method of policy analysis. It emphasises making policy transparently, with substantive Māori (Indigenous peoples of New Zealand) leadership. It is becoming increasingly influential among policy makers in New Zealand with the potential to counter racism as a modifiable determinant of health, for example.
Keywords: Public Policy; Te Tiriti o Waitangi

Chapter 2: What is decolonisation? - Mercier, Ocean Ripeka (Imagining Decolonisation, 2020)

Radio Spectrum: Managing Tension between Kāwanatanga and Tino Rangatiratanga (2012) - Winiata, Whatarangi (The Survival of Māori As a People, 2021)
This collection brings together over forty years of thought and comment by Dr Whatarangi Winiata on Māori spirituality, social development, education and political affairs. Each chapter discusses the importance andimpact of Māori management of Māori matters and the ongoing pursuit of tino rangatiratanga in all areas of life. Dr Winiata has worked to achieve Māori development, wellbeing and attainment of aspirations over decades: driving the iwi development programme Whakatupuranga Rua Mano that led to the foundation of the first contemporary wānanga, Te Wānanga o Raukawa; being key in restructuring the working of Te Hāhi Mihingare; galvanising the New Zealand Māori Council to hold the Crown accountable over fisheries, forestry, languageand broadcasting; and co-founding the Māori Party with Dame Tariana Turia and Sir Pita Sharples. Thesepapers, curated by Dr Winiata and Daphne Luke, provide an analysis of recent Māori experience, pursuit ofself-determination and history of Aotearoa.

In Pursuit of Te Tiriti o Waitangi (2010) - Winiata, Whatarangi (The Survival of Māori As a People, 2021)
This collection brings together over forty years of thought and comment by Dr Whatarangi Winiata on Māori spirituality, social development, education and political affairs. Each chapter discusses the importance andimpact of Māori management of Māori matters and the ongoing pursuit of tino rangatiratanga in all areas of life. Dr Winiata has worked to achieve Māori development, wellbeing and attainment of aspirations over decades: driving the iwi development programme Whakatupuranga Rua Mano that led to the foundation of the first contemporary wānanga, Te Wānanga o Raukawa; being key in restructuring the working of Te Hāhi Mihingare; galvanising the New Zealand Māori Council to hold the Crown accountable over fisheries, forestry, languageand broadcasting; and co-founding the Māori Party with Dame Tariana Turia and Sir Pita Sharples. Thesepapers, curated by Dr Winiata and Daphne Luke, provide an analysis of recent Māori experience, pursuit ofself-determination and history of Aotearoa.

The Reconciliation of Kāwanatanga and Tino Rangatiratanga (Rua Rautau Lecture, 2005) - Winiata, Whatarangi (The Survival of Māori As a People, 2021)
This collection brings together over forty years of thought and comment by Dr Whatarangi Winiata on Māori spirituality, social development, education and political affairs. Each chapter discusses the importance andimpact of Māori management of Māori matters and the ongoing pursuit of tino rangatiratanga in all areas of life. Dr Winiata has worked to achieve Māori development, wellbeing and attainment of aspirations over decades: driving the iwi development programme Whakatupuranga Rua Mano that led to the foundation of the first contemporary wānanga, Te Wānanga o Raukawa; being key in restructuring the working of Te Hāhi Mihingare; galvanising the New Zealand Māori Council to hold the Crown accountable over fisheries, forestry, languageand broadcasting; and co-founding the Māori Party with Dame Tariana Turia and Sir Pita Sharples. Thesepapers, curated by Dr Winiata and Daphne Luke, provide an analysis of recent Māori experience, pursuit ofself-determination and history of Aotearoa.

Proposals for Parliamentary Arrangements under Te Tiriti o Waitangi (1996) - Winiata, Whatarangi (The Survival of Māori As a People, 2021)
This collection brings together over forty years of thought and comment by Dr Whatarangi Winiata on Māori spirituality, social development, education and political affairs. Each chapter discusses the importance andimpact of Māori management of Māori matters and the ongoing pursuit of tino rangatiratanga in all areas of life. Dr Winiata has worked to achieve Māori development, wellbeing and attainment of aspirations over decades: driving the iwi development programme Whakatupuranga Rua Mano that led to the foundation of the first contemporary wānanga, Te Wānanga o Raukawa; being key in restructuring the working of Te Hāhi Mihingare; galvanising the New Zealand Māori Council to hold the Crown accountable over fisheries, forestry, languageand broadcasting; and co-founding the Māori Party with Dame Tariana Turia and Sir Pita Sharples. Thesepapers, curated by Dr Winiata and Daphne Luke, provide an analysis of recent Māori experience, pursuit ofself-determination and history of Aotearoa.

Mamae Māori, Progress and Proposals for Development (1987) - Winiata, Whatarangi (The Survival of Māori As a People, 2021)
This collection brings together over forty years of thought and comment by Dr Whatarangi Winiata on Māori spirituality, social development, education and political affairs. Each chapter discusses the importance andimpact of Māori management of Māori matters and the ongoing pursuit of tino rangatiratanga in all areas of life. Dr Winiata has worked to achieve Māori development, wellbeing and attainment of aspirations over decades: driving the iwi development programme Whakatupuranga Rua Mano that led to the foundation of the first contemporary wānanga, Te Wānanga o Raukawa; being key in restructuring the working of Te Hāhi Mihingare; galvanising the New Zealand Māori Council to hold the Crown accountable over fisheries, forestry, languageand broadcasting; and co-founding the Māori Party with Dame Tariana Turia and Sir Pita Sharples. Thesepapers, curated by Dr Winiata and Daphne Luke, provide an analysis of recent Māori experience, pursuit ofself-determination and history of Aotearoa.

Chapter Eighteen: Sharing Power: Māori and Protect Areas - Mead, Aroha Te Pareake (Future challenges for Māori: he kōrero anamata, 2013)
"This collection of essays by 22 contributors, experts in their fields, represents the accumulated knowledge of a group of Māori scholars on a variety of contemporary issues, including Māori identity and self-determination, the environment, te reo Māori, education, social and economic issues, and governance and leadership. The collection is a result of a series of seminars organised by the MANU AO Academy, which is a national inter-university Māori Academy for academic and professional advancement"–Publisher information.
Keywords: government; mana motuhake; rangatiratanga; social conditions; sovereignty

Emerging Socities AD 1500-1800’ - Anderson, Atholl (Tangata Whenua: A History, 2015)

Ka Tika A Muri, Ka Tika A Mua? Māori protest politics and the Treaty of Waitangi settlement process - Poata-Smith, Evan Te Ahu (Tangata, Tangata: the changing ethnic contours of New Zealand, 2004)

The World Conference on Indigenous Peoples 2014 - Whare, Tracey (International Indigenous Rights in Aotearoa New Zealand, 2017)
In Aotearoa New Zealand the ways in which indigenous claims to lands and waters are addressed are often looked to as good, or even best, practice by indigenous peoples around the world. While things are far from perfect, in recent decades Maori have succeeded in changing perceptions about the Treaty of Waitangi as the foundation of the nation, and work steadily continues on settling outstanding Treaty claims. The resulting Treaty of Waitangi settlements are negotiated arrangements which aim to remove a sense of historical grievance and achieve significant rebuilding of the Maori economy. They are seen by some as dynamic and powerful steps towards economic independence, as a means of recognising special relationships to lands and waters, and a necessary prerequisite to improved relationships between the state and the indigenous Maori in the future. ¹ Critics see the settlements and the processes followed to reach them as too heavily weighted in the government's favour. ² They argue that the settlements do not sufficiently compensate for actual losses. They are said to pit Maori against Maori. Diverse claimant groups are effectively forced to negotiate within standardised and fixed parameters. For these and other reasons, the settlement agreements, policies and processes have been labelled as divisive and compromising self-determination. ³
Keywords: tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

The UN Special Procedures and Indigenous Peoples' Rights - Te Aho, Fleur (International Indigenous Rights in Aotearoa New Zealand, 2017)
In Aotearoa New Zealand the ways in which indigenous claims to lands and waters are addressed are often looked to as good, or even best, practice by indigenous peoples around the world. While things are far from perfect, in recent decades Maori have succeeded in changing perceptions about the Treaty of Waitangi as the foundation of the nation, and work steadily continues on settling outstanding Treaty claims. The resulting Treaty of Waitangi settlements are negotiated arrangements which aim to remove a sense of historical grievance and achieve significant rebuilding of the Maori economy. They are seen by some as dynamic and powerful steps towards economic independence, as a means of recognising special relationships to lands and waters, and a necessary prerequisite to improved relationships between the state and the indigenous Maori in the future. ¹ Critics see the settlements and the processes followed to reach them as too heavily weighted in the government's favour. ² They argue that the settlements do not sufficiently compensate for actual losses. They are said to pit Maori against Maori. Diverse claimant groups are effectively forced to negotiate within standardised and fixed parameters. For these and other reasons, the settlement agreements, policies and processes have been labelled as divisive and compromising self-determination. ³
Keywords: tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

Gender, Populism and Jacinda Ardern - Curtin, Jennifer; Greaves, Lara (A Populist Exception? : The 2017 New Zealand General Election / Edited By Jack Vowles and Jennifer Curtin., 2020)
Keywords: Elections & referenda; New Zealand; authoritarianism; elections; inclusivity; politics; populism; vote choice

Coming Home? Māori Voting in 1999 - Sullivan, Ann; Margaritis, Dimitri (Proportional representation on trial, 2002)
Keywords: Coalition governments – New Zealand; Elections – New Zealand; New Zealand – Politics and government – 1996-; New Zealand Parliament – Elections; 1999; Political campaigns – New Zealand; Proportional representation – New Zealand

A 'Team of Five Million'?: Covid-19 and the 2020 New Zealand General Election - Curtin, Jennifer.; Greaves, Lara.; Vowles, Jack (A Team of Five Million? : The 2020 'Covid-19' New Zealand General Election., 2024)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 1972-; New Zealand Parliament – Elections; 2020; Political campaigns

Gendering Leadership and Policy during Covid-19: Jacinda Ardern and the Women's Vote - Curtin, Jennifer.; Woodman, V.K.G.; Greaves, Lara (A Team of Five Million? : The 2020 'Covid-19' New Zealand General Election., 2024)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 1972-; New Zealand Parliament – Elections; 2020; Political campaigns

The Disappearing 'Team of Five Million'?: The Road to the 2023 Election - Curtin, Jennifer.; Greaves, Lara.; Vowles, Jack (A Team of Five Million? : The 2020 'Covid-19' New Zealand General Election., 2024)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 1972-; New Zealand Parliament – Elections; 2020; Political campaigns

Māori Affairs and Public Policy - Sullivan, Ann (New Zealand government and politics, 2003)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 1972-; New Zealand Parliament – Elections; 2002; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

Mana Māori Motuhake: The State of the Māori Nation - Durie, Mason (New Zealand government and politics, 2003)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 1972-; New Zealand Parliament – Elections; 2002; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

Māori Participation - Sullivan, Kaapua (New Zealand government & politics, 2010)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 1972-; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

Māori Party - Smith, Kaapua (New Zealand Government & Politics, 2010)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 1972-; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

Māori Policy and Politics - Sullivan, Ann (New Zealand government & politics, 2006)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 1972-; New Zealand Parliament – Elections; 2005; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

Māori Party - Smith, Kaapua (New Zealand government & politics, 2006)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 1972-; New Zealand Parliament – Elections; 2005; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

Youth Engagement - Tawhai, Veronica (New Zealand government and politics, 2015)
Keywords: Elections – New Zealand; Financial crises – New Zealand; Global Financial Crisis; 2008-2009; Māori (New Zealand people) – Politics and government; Nationalism – New Zealand; New Zealand – Foreign relations; New Zealand – Politics and government; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

The Māori Party - Godfery, Morgan (New Zealand government and politics, 2015)
Keywords: Elections – New Zealand; Financial crises – New Zealand; Global Financial Crisis; 2008-2009; Māori (New Zealand people) – Politics and government; Nationalism – New Zealand; New Zealand – Foreign relations; New Zealand – Politics and government; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

The Treaty of Waitangi - Mulholland, Malcolm (New Zealand government and politics, 2015)
Keywords: Elections – New Zealand; Financial crises – New Zealand; Global Financial Crisis; 2008-2009; Māori (New Zealand people) – Politics and government; Nationalism – New Zealand; New Zealand – Foreign relations; New Zealand – Politics and government; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

Māori Political History 1860-1960 - Stevens, Michael J. (New Zealand government and politics, 2015)
Keywords: Elections – New Zealand; Financial crises – New Zealand; Global Financial Crisis; 2008-2009; Māori (New Zealand people) – Politics and government; Nationalism – New Zealand; New Zealand – Foreign relations; New Zealand – Politics and government; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

The Constitution - Jones, Carwyn (Government and politics in Aotearoa New Zealand, 2024)
Keywords: Elections – New Zealand; Māori (New Zealand people) – Politics and government; New Zealand – Foreign relations; New Zealand – Politics and government; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand; Tōrangapū

Te Tiriti o Waitangi - Godfery, Morgan; Hayward, Janine (Government and politics in Aotearoa New Zealand, 2024)
Keywords: Elections – New Zealand; Māori (New Zealand people) – Politics and government; New Zealand – Foreign relations; New Zealand – Politics and government; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand; Tōrangapū

Marxism - Poata-Smith, Evan (Government and politics in Aotearoa New Zealand, 2021)
Keywords: Elections – New Zealand; Māori (New Zealand people) – Politics and government; New Zealand – Foreign relations; New Zealand – Politics and government; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand; Tōrangapū

The Importance of Political Theory - O'Sullivan, Dominic (Government and politics in Aotearoa New Zealand, 2021)
Keywords: Elections – New Zealand; Māori (New Zealand people) – Politics and government; New Zealand – Foreign relations; New Zealand – Politics and government; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand; Tōrangapū

Māori Political Histories - Greaves, Lara (Government and politics in Aotearoa New Zealand, 2024)
Keywords: Elections – New Zealand; Māori (New Zealand people) – Politics and government; New Zealand – Foreign relations; New Zealand – Politics and government; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand; Tōrangapū

Māori Representation in Local Government - Sullivan, Ann (Local government and the Treaty of Waitangi, 2003)
Keywords: Kāwanatanga; Local government – New Zealand; Māori; Māori (New Zealand people) – Government relations; New Zealand Resource Management Act 1991; Resource Management Act 1991 (New Zealand); Tiriti o Waitangi; Treaty of Waitangi (1840 February 6)

Local Government and the Waitangi Tribunal - Hemi, Murray (Local government and the Treaty of Waitangi, 2003)
Keywords: Kāwanatanga; Local government – New Zealand; Māori; Māori (New Zealand people) – Government relations; New Zealand Resource Management Act 1991; Resource Management Act 1991 (New Zealand); Tiriti o Waitangi; Treaty of Waitangi (1840 February 6)

Appendix to Chapter 2: Kaitiakitanga: A Commentary on the Resource Management Act - Tutua-Nathan, Tikitu (Local government and the Treaty of Waitangi, 2003)
Keywords: Kāwanatanga; Local government – New Zealand; Māori; Māori (New Zealand people) – Government relations; New Zealand Resource Management Act 1991; Resource Management Act 1991 (New Zealand); Tiriti o Waitangi; Treaty of Waitangi (1840 February 6)

Resource Management, Local Government, and the Treaty of Waitangi - Love, Morris Te Whiti (Local government and the Treaty of Waitangi, 2003)
Keywords: Kāwanatanga; Local government – New Zealand; Māori; Māori (New Zealand people) – Government relations; New Zealand Resource Management Act 1991; Resource Management Act 1991 (New Zealand); Tiriti o Waitangi; Treaty of Waitangi (1840 February 6)

Financial and Commercial Dimensions of Settlements - Stone, Damian (Treaty of Waitangi settlements, 2015)
Keywords: Kerēme (Tiriti o Waitangi); Mana whenua; Māori (New Zealand people) – Claims; Māori (New Zealand people) – Government relations; Māori (New Zealand people) – Land tenure; Tiriti o Waitangi; Treaty of Waitangi (1840 February 6); Whakatau mauri; Whenua tautohetohe

Settlements and 'Taonga' A Ngāi Tahu Commentary - Stevens, Michael J. (Treaty of Waitangi settlements, 2015)
Keywords: Kerēme (Tiriti o Waitangi); Mana whenua; Māori (New Zealand people) – Claims; Māori (New Zealand people) – Government relations; Māori (New Zealand people) – Land tenure; Tiriti o Waitangi; Treaty of Waitangi (1840 February 6); Whakatau mauri; Whenua tautohetohe

Māori Governance and Accountability - Hall, Evan (The Waitangi Tribunal Te Roopu Whakamana i te Tiriti o Waitangi, 2015)

The Changing Contours of Maori Identity and the Treaty Settlement Process - Poata-Smith, Evan (The Waitangi Tribunal Te Roopu Whakamana i te Tiriti o Waitangi, 2004)

The Environmental Reports - Wheen, Nicola; Ruru, Jacinta (The Waitangi Tribunal Te Roopu Whakamana i te Tiriti o Waitangi, 2015)

The Fisheries Reports - Milroy, Stephanie (The Waitangi Tribunal Te Roopu Whakamana i te Tiriti o Waitangi, 2015)

Epilogue: Te Tiriti Relationships - A Critical Reflection - Stanton-Turei, Metiria (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) – Civil rights.; Māori (New Zealand people) – Government relations.; Māori (New Zealand people) – Legal status; laws; etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

Beyond Treaty Principles: The Double Trusteeship of te Tiriti o Waitangi - Kawharu, Merata (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) – Civil rights.; Māori (New Zealand people) – Government relations.; Māori (New Zealand people) – Legal status; laws; etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

Whakarongo ki te tangi o tō tātou Kaitiaki: The Cry of Our Harbour Custodians - Muru-Lanning, Marama; Lanning, Gerald (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) – Civil rights.; Māori (New Zealand people) – Government relations.; Māori (New Zealand people) – Legal status; laws; etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

The Enduring Power of Hope: The Impact of the Treaty Settlement Process in Te Tauihu - Johnston, Kerena (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) – Civil rights.; Māori (New Zealand people) – Government relations.; Māori (New Zealand people) – Legal status; laws; etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

Mana Whenua in Twenty-first Century Aotearoa New Zealand - Kohu-Morris, Jacobi (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) – Civil rights.; Māori (New Zealand people) – Government relations.; Māori (New Zealand people) – Legal status; laws; etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

A Modern-day Muru: The Saga of the Wairarapa Moana and Pouākani Whenua - Stanton-Turei, Metiria (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) – Civil rights.; Māori (New Zealand people) – Government relations.; Māori (New Zealand people) – Legal status; laws; etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

Ihumātao and te Tiriti: Striving for Just Relationships - Jones, Carwyn; Lee-Morgan, Jenny; Hancock, Frances; Matata-Sipu, Qiane; Newton, Pania; Waa, Moana; Short, Nicola; McCreanor, Tim (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) – Civil rights.; Māori (New Zealand people) – Government relations.; Māori (New Zealand people) – Legal status; laws; etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

A Treaty Breach 'Born of Hostility to the Promise Itself': Tamariki, Whānau and te Tiriti - Fitzmaurice-Brown, Luke (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) – Civil rights.; Māori (New Zealand people) – Government relations.; Māori (New Zealand people) – Legal status; laws; etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

The Treaty of Waitangi in Policy Development - Pirini, Mihiata (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) – Civil rights.; Māori (New Zealand people) – Government relations.; Māori (New Zealand people) – Legal status; laws; etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

Propagating the Myth that Māori Ceded Sovereignty - McCreanor, Tim; Came, Heather; Berghan, Grant (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Keywords: Kāwanatanga.; Mana whakahaere.; Māori (New Zealand people) – Civil rights.; Māori (New Zealand people) – Government relations.; Māori (New Zealand people) – Legal status; laws; etc.; Noho a-iwi.; Tiriti o Waitangi.; Treaty of Waitangi

Tu Māori Mai: The Māori Party Campaign - Flavell, Te Ururoa (Moments of truth : the New Zealand general election of 2014, 2015)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 21st century; New Zealand Parliament – Elections; 2014; Political campaigns – Press coverage – New Zealand; Voting – New Zealand

Māori in Australia and the 2011 Election and Referendum - Bargh, Maria (Kicking the tyres : the New Zealand general election and electoral referendum of 2011, 2012)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 21st century; New Zealand Parliament – Elections; 2011; Political parties – New Zealand; Proportional representation – New Zealand; Referendum – New Zealand; Representative government and representation – New Zealand

The Fragmentation of Māori Politics - Godfery, Morgan (Kicking the tyres : the New Zealand general election and electoral referendum of 2011, 2012)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 21st century; New Zealand Parliament – Elections; 2011; Political parties – New Zealand; Proportional representation – New Zealand; Referendum – New Zealand; Representative government and representation – New Zealand

The Māori Party - Smith, Kaapua (Kicking the tyres : the New Zealand general election and electoral referendum of 2011, 2012)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 21st century; New Zealand Parliament – Elections; 2011; Political parties – New Zealand; Proportional representation – New Zealand; Referendum – New Zealand; Representative government and representation – New Zealand

Mana - Minto, John; Potter, Helen; Sykes, Annette (Kicking the tyres : the New Zealand general election and electoral referendum of 2011, 2012)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 21st century; New Zealand Parliament – Elections; 2011; Political parties – New Zealand; Proportional representation – New Zealand; Referendum – New Zealand; Representative government and representation – New Zealand

The Maori Party - Katene, Rahui (Key to victory : the New Zealand general election of 2008, 2010)
Keywords: Coalition governments – New Zealand; Elections – New Zealand; Key; John; 1961-; New Zealand – Politics and government – 21st century; New Zealand Parliament – Elections; 2008; Political campaigns – Press coverage – New Zealand; Proportional representation – New Zealand; Voting – New Zealand

The Maori Party - Sharples, Pita (The baubles of office : the New Zealand general election of 2005, 2007)
Keywords: New Zealand – Politics and government – 1996-; New Zealand Parliament – Elections; 2005

Campaigning in the Maori Seats: Talking to Ourselves and Past Each Other - Bargh, Maria (The baubles of office : the New Zealand general election of 2005, 2007)
Keywords: New Zealand – Politics and government – 1996-; New Zealand Parliament – Elections; 2005

Towards a United and Proud Aotearoa - Jones, Shane (The baubles of office : the New Zealand general election of 2005, 2007)
Keywords: New Zealand – Politics and government – 1996-; New Zealand Parliament – Elections; 2005

19. Mātiro Whakamua: Looking Over the Horizon - Bargh, Maria; MacArthur, Julie (Environmental politics and policy in Aotearoa New Zealand, 2022)
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

18. Te Mana o te Wai: The Modern Politics of Freshwater - Ruru, Jacinta (Environmental politics and policy in Aotearoa New Zealand, 2022)
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

15. Imperialism and Systems of Stuff - Ngata, Tina (Environmental politics and policy in Aotearoa New Zealand, 2022)
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

14. Te Taiao and 'Biodiversity' - Bargh, Maria; Malcolm, Tame (Environmental politics and policy in Aotearoa New Zealand, 2022)
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

11. How to Write a Press Release - Tapsell, Ellen (Environmental politics and policy in Aotearoa New Zealand, 2022)
Environmental Politics and Policy in Aotearoa New Zealand is a comprehensive introduction to confronting some of today's most urgent challenges. Global warming, threats to biodiversity, contamination of waterways and other environmental issues confront today's citizens with critical challenges that are fundamentally political. Power, authority and state action enable current practices - and through politics and policy that power can be harnessed to create a more ecologically sustainable planet. In this book, leading scholars from around Aotearoa introduce students to environmental politics and policy based in this country's unique institutional, cultural and resource context. The text focuses on the key importance of Te Tiriti o Waitangi, the characteristics of the natural environment in Aotearoa and the role of gender dynamics in the distribution of power, before turning to how this unique setting informs and is, in turn, informed by the global context of environmental politics. The authors take a systemic view of environmental politics and governance in New Zealand, addressing the philosophical and ideational debates about who and what matters (both human and non-human), the political institutions that embed and enact these ideas, and how these ideas then manifest in particular arenas - from climate and freshwater to energy and farming. Practical tips - how to make a submission, organise a protest, write a policy brief or a press release - are woven throughout.
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

10. Social Movements and the Environment - Kurian, Priya; Cretney, Raven; Munshi, Debashish; Morrison, Sandra L. (Environmental politics and policy in Aotearoa New Zealand, 2022)
Environmental Politics and Policy in Aotearoa New Zealand is a comprehensive introduction to confronting some of today's most urgent challenges. Global warming, threats to biodiversity, contamination of waterways and other environmental issues confront today's citizens with critical challenges that are fundamentally political. Power, authority and state action enable current practices - and through politics and policy that power can be harnessed to create a more ecologically sustainable planet. In this book, leading scholars from around Aotearoa introduce students to environmental politics and policy based in this country's unique institutional, cultural and resource context. The text focuses on the key importance of Te Tiriti o Waitangi, the characteristics of the natural environment in Aotearoa and the role of gender dynamics in the distribution of power, before turning to how this unique setting informs and is, in turn, informed by the global context of environmental politics. The authors take a systemic view of environmental politics and governance in New Zealand, addressing the philosophical and ideational debates about who and what matters (both human and non-human), the political institutions that embed and enact these ideas, and how these ideas then manifest in particular arenas - from climate and freshwater to energy and farming. Practical tips - how to make a submission, organise a protest, write a policy brief or a press release - are woven throughout.
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

3. Environmental Ideas in Aotearoa - Mutu, Margaret (Environmental politics and policy in Aotearoa New Zealand, 2022)
Environmental Politics and Policy in Aotearoa New Zealand is a comprehensive introduction to confronting some of today's most urgent challenges. Global warming, threats to biodiversity, contamination of waterways and other environmental issues confront today's citizens with critical challenges that are fundamentally political. Power, authority and state action enable current practices - and through politics and policy that power can be harnessed to create a more ecologically sustainable planet. In this book, leading scholars from around Aotearoa introduce students to environmental politics and policy based in this country's unique institutional, cultural and resource context. The text focuses on the key importance of Te Tiriti o Waitangi, the characteristics of the natural environment in Aotearoa and the role of gender dynamics in the distribution of power, before turning to how this unique setting informs and is, in turn, informed by the global context of environmental politics. The authors take a systemic view of environmental politics and governance in New Zealand, addressing the philosophical and ideational debates about who and what matters (both human and non-human), the political institutions that embed and enact these ideas, and how these ideas then manifest in particular arenas - from climate and freshwater to energy and farming. Practical tips - how to make a submission, organise a protest, write a policy brief or a press release - are woven throughout.
Keywords: environment; environmental conditions; environmental protection; government relations; social conditions; tiriti o waitangi/treaty of waitangi

Intersections of race, gender and social policy in Aotearoa/New Zealand: Waihi I te toipoto, kaua I te toiroa - McIntosh, Tracey (Racism and public policy, 2005)

Māori and the Crown: Obstructing Indigenous Identity in Aotearoa-New Zealand - Muru-Lanning, Marama (Remediating Cartographies of Erasure: Anthropology, Indigenous Epistemologies, and the Global Imaginary, 2025)

Colonization and the importation of ideologies of race, gender, and class in Aotearoa - Pihama, Leonie (Handbook of Indigenous education, 2018)

Co-Management in Theory and Practice: Co-Managing the Waipā River - Parsons, Meg; Fisher, Karen; Crease, Roa Petra (Decolonising Blue Spaces in the Anthropocene: Freshwater management in Aotearoa New Zealand, 2021)

Transforming river governance: The co-governance arrangements in the Waikato and Waipa Rivers - Parsons, Meg; Fisher, Karen; Crease, Roa Petra (Decolonising Blue Spaces in the Anthropocene: Freshwater management in Aotearoa New Zealand, 2021)

Indigenous peoples and climate change: Australia and New Zealand - Nursey-Bray, Melissa; Parsons, Meg (Climate Action, 2021)

Kaupapa Māori Politics - Te One, Annie (Government and Politics in Aotearoa and New Zealand, 2021)
Keywords: Kaupapa Māōri; Tikanga

Post Colonialism - O'Sullivan, Dominic (New Zealand Government and Politics, 2015)
Keywords: New Zealand-Politics and government-1972-

Riro Whenua Atu, Hoki Whenua Mai: Land Grabbing in British Settler States and Contested Land Restitution to Māori in Aotearoa New Zealand - Mutu, Margaret (Routledge Handbook of Global Land and Resource Grabbing, 2023)
The British relied on the legal fiction known as the Doctrine of Discovery to dispossess Māori of Aotearoa New Zealand and the Indigenous Peoples of Canada, the United States and Australia and to violently take over their territories. British colonisation continues to severely disadvantage these Indigenous Peoples who have never given up their fight to recover their lands, resources, and power. This chapter draws on the work of Indigenous scholars to provide a very brief overview of just some of the methods adopted by the British to dispossess the Indigenous Peoples of Canada, the United States and Australia and the struggles in those countries to achieve land restitution. It then considers the situation for Māori in more detail. It provides an overview of the schemes the British dreamt up to steal Māori land and the steps Māori have taken as we tried to achieve land and resource restitution over the past century.
Keywords: Colonisation; Dispossession; Restitution

Resisting the Red Wave? The Māori Party’s return to parliament - Greaves, Lara; Morgan, Ella; Hayward, Janine (A Team of Five Million?: The 2020 ‘Covid-19’ New Zealand General Election, 2024)
Keywords: Māori Party; Māori voters; Voting; Parties; Parliament

Pebbles in Shoes? The Māori Electorates in 2023 - Greaves, Lara (Back on Track? The New Zealand General Election of 2023, 2024)
Keywords: Māori electorates; Voting; Parties; Parliament

Chapter 11: The United Nations Declaration on the Rights of Indigenous Peoples and te Tiriti Relationships - Charters, Claire; Te Aho, Fleur; Whare, Tracey (Te Tiriti o Waitangi relationships: people, politics and law, 2024)
Summary: "The third in a series committed to discussions of Te Tiriti o Waitangi/Treaty of Waitangi issues. These essays from leading scholars and researchers take a dynamic approach to understanding Tiriti/Treaty relationships, acknowledging the ever-evolving interplay between the Crown and Māori through time. The book addresses pressing issues like Treaty principles, sovereignty, the UN Declaration on the Rights of Indigenous Peoples, and manawhenua relationships to Te Tiriti and settlements. It emphasises the roles of tikanga and rangatiratanga in fostering genuine progress, and envisions a future guided by these principles in advancing Māori-Crown relationships"–Publisher's website.
Keywords: Kāwanatanga; Mana whakahaere; Māori – Civil rights; Māori – Government relations; Māori – Legal status; laws; etc; Mātāpono; Noho-ā-iwi; Tiriti o Waitangi; Treaty of Waitangi (1840 February 6)

Chapter 6: Contemporary critical legal accounts of the relationship between international law and domestic law and policy - Charters, Claire; Aho, Fleur Te; Whare, Tracey (Handbook of Indigenous Public Policy, 2024)
This chapter outlines juris-significant, but unorthodox, ways in which international and domestic law, policy and practice influence each other with respect to Indigenous Peoples’ norms. In the authors’ view, such an approach paints a more comprehensive and accurate picture of the legal dialogue that occurs than orthodox and positivistic legal accounts. The approach also illustrates unique and potentially powerful ways that Indigenous Peoples and other non-state actors can better realise Indigenous Peoples’ rights in their territories. The chapter begins by briefly introducing international legal norms relevant to Indigenous Peoples before contrasting formal understandings of the law with new accounts of the influence of legal norms. The final, and primary, section seeks to capture the relationship between international law and domestic state law and policy. It focuses upon international law’s relationship with the courts, legislature and the executive in Aotearoa (New Zealand), although the broader existence of this intersect is signalled.

Whānau Ora: An Indigenous policy success story - Boulton, Amohia; Smith, Verna; Moore, Charlotte; Cumming, Jacqueline (Successful Public Policy: Lessons from Australia and New Zealand, 2019)
Keywords: Health; Māori; Māori Health; Public Policy; Whanau Ora

Kaupapa maori research - Smith, Linda Tuhiwai Te Rina (Reclaiming Indigenous Voice and Vision, 2000)

Culture and Ethnicity: what is the question? - Wepa, Dianne (Cultural safety in Aotearoa New Zealand, 2015)
In this second edition of Cultural Safety in Aotearoa New Zealand, editor Dianne Wepa presents a range of theoretical and practice-based perspectives adopted by experienced educators who are active in cultural safety education. Dianne Wepa, Hawkes Bay District Health Board, NZ.
Keywords: bicultural; ethnic identity; ethnicity

Te Tiriti o Waitangi/Treaty of Waitangi 1840: its influence on health practice - Wilson, Denise; Haretuku, Riripeti (Cultural safety in Aotearoa New Zealand, 2015)
In this second edition of Cultural Safety in Aotearoa New Zealand, editor Dianne Wepa presents a range of theoretical and practice-based perspectives adopted by experienced educators who are active in cultural safety education. Dianne Wepa, Hawkes Bay District Health Board, NZ.
Keywords: bicultural; health; tiriti o waitangi/treaty of waitangi; treaty principles

Gender, Politics, and the State, and the Māori - Houkamau, Carla (The Wiley Blackwell Encyclopedia of Gender and Sexuality Studies, 2016)
A diversity of perspectives and wide variety of cultural and social features characterize Māori society and there is no one consensus view held by Māori in relation to gender roles, political orientations, or Māori/government (or state) relations. Both Māori women and men have shared in the struggle to assert Māori resistance to colonial encroachment and one gender cannot be elevated over the other. Moreover, Māori views and perspectives on the different roles of Māori men and women are contested and differ tribally and between individuals. This entry describes aspects of precolonial Māori society that shaped traditional values and discusses key sociohistorical factors shaping gender roles among Māori. A focus on the contribution of Māori women to Māori development and advancement is offered. The relationship between Māori identity, culture, and the New Zealand government (or state) is highlighted throughout.
Keywords: crown policy; cultural practices; gender; identity; mana wāhine

Chapter 11: Maori Concepts and Practices of Rangatiratanga: "Sovereignty?" - Tomas, Nin (Sovereignty: Frontiers of Possibility, 2013)
Keywords: rangatiratanga; sovereignty; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi

Chapter 3: Citizenship Education: Rangatahi Electoral Participation - Tawhai, Veronica (Mana tangata politics of empowerment, 2011)
This is a collection of papers by senior Maori academics who are experts and have considerable mana in their chosen fields. The ten contributing authors, who are academics at Massey University, discuss the Maori language, marae, religion, the Treaty of Waitangi, the State and Maori, citizenship education, mental health, the health workforce, kaitiakitanga and horticulture. The book discusses Maori development and contemporary issues concerning Maori, both from the authors' perspectives and across different disciplines.
Keywords: elections; rangatahi; tiriti o waitangi/treaty of waitangi; voting

Chapter 2: Te Tiriti o Waitangi: A Blueprint for the Future - Campbell, Bronwyn (Mana tangata politics of empowerment, 2011)
This is a collection of papers by senior Maori academics who are experts and have considerable mana in their chosen fields. The ten contributing authors, who are academics at Massey University, discuss the Maori language, marae, religion, the Treaty of Waitangi, the State and Maori, citizenship education, mental health, the health workforce, kaitiakitanga and horticulture. The book discusses Maori development and contemporary issues concerning Maori, both from the authors' perspectives and across different disciplines.
Keywords: tiriti o waitangi/treaty of waitangi; treaty principles

Chapter 1: Colonial Theories of the State: Māori/State Relations - Tomlins-Jahnke, Huia (Mana tangata politics of empowerment, 2011)
This is a collection of papers by senior Maori academics who are experts and have considerable mana in their chosen fields. The ten contributing authors, who are academics at Massey University, discuss the Maori language, marae, religion, the Treaty of Waitangi, the State and Maori, citizenship education, mental health, the health workforce, kaitiakitanga and horticulture. The book discusses Maori development and contemporary issues concerning Maori, both from the authors' perspectives and across different disciplines.
Keywords: constitution; imperialism; tiriti o waitangi/treaty of waitangi

Chapter 12: The Post-settlement World (So Far): Impacts for Māori - Bargh, Maria (Treaty of Waitangi settlements, 2015)
Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: post-settlement (waitangi tribunal); tiriti o waitangi/treaty of waitangi; treaty settlements

Chapter 11: Unsettling Treaty Settlements: Contemporary Māori Identity and Representation Challenges - Joseph, Robert (Treaty of Waitangi settlements, 2015)
Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: crown policy; identity; tiriti o waitangi/treaty of waitangi; treaty settlements

Chapter 8: 'The sea I never gave': Fisheries Settlements - Mutu, Margaret (Treaty of Waitangi settlements, 2015)
Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: fisheries; tiriti o waitangi/treaty of waitangi; treaty settlements

Chapter 7: Ngā Whakataunga Waimāori: Freshwater Settlements - Te Aho, Linda (Treaty of Waitangi Settlements, 2015)
Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: tiriti o waitangi/treaty of waitangi; treaty settlements; water management

Chapter 6: 'O ratou wenua': Land and Estate Settlements - Warbrick, Paerau (Treaty of Waitangi settlements, 2015)
Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: mana whenua; tiriti o waitangi/treaty of waitangi; treaty settlements

Chapter 11: Parliamentary Devolution and Māori Self-Governance - Durie, Mason (Ngā Kahui Pou Launching Maori Futures, 2013)
By 2051 the ethnic Maori population will almost double in size to close to a million, or twenty-two percent of the total New Zealand population. Even more dramatically, by 2051 thirty-three percent of all children in the country will be Maori?' This substantial change in our society will have major implications for Maori and wider society. Professor Durie discusses traditions and customs and addresses contemporary needs in order to build development strategies for the launch of the Maori population into the new millennium.
Keywords: crown policy; parliament; rangatiratanga; self-governance

Chapter 7: A Framework for Considering Constitutional Change and the Position of Māori in Aotearoa - Durie, Mason (Ngā Kahui Pou Launching Maori Futures, 2013)
By 2051 the ethnic Maori population will almost double in size to close to a million, or twenty-two percent of the total New Zealand population. Even more dramatically, by 2051 thirty-three percent of all children in the country will be Maori?' This substantial change in our society will have major implications for Maori and wider society. Professor Durie discusses traditions and customs and addresses contemporary needs in order to build development strategies for the launch of the Maori population into the new millennium.
Keywords: constitutional transformation; tiriti o waitangi/treaty of waitangi

Chapter 8: Māori in Governance: Parliament, Statutory Recognition, and the State Sector - Durie, Mason (Ngā Kahui Pou Launching Maori Futures, 2013)
By 2051 the ethnic Maori population will almost double in size to close to a million, or twenty-two percent of the total New Zealand population. Even more dramatically, by 2051 thirty-three percent of all children in the country will be Maori?' This substantial change in our society will have major implications for Maori and wider society. Professor Durie discusses traditions and customs and addresses contemporary needs in order to build development strategies for the launch of the Maori population into the new millennium.
Keywords: māori electorates; māori seats; tiriti o waitangi/treaty of waitangi

Globalisation and the Colonising State of Mind - Jackson, Moana (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: colonisation; globalisation; neoliberalism; protest

Māori and the United Nations - Charters, Claire (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: UNDRIP; globalisation; neoliberalism; protest; united nations

A Small Issue of Sovereignty - Bargh, Maria (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: history; neoliberalism; political Ideologies; protest; sovereignty; tino rangatiratanga; trans-pacific partnership

We Are Everywhere - Bargh, Maria; Tuiono, Teanau (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: activism; neoliberalism; protest; tino rangatiratanga

Blunting the System: The Personal is Political - Sykes, Annette (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: activism; law; neoliberalism; waitangi tribunal

Chapter 7: Papaki Rua Ngā Tai: Tides of Confluence: Māori and the State - Durie, Mason (Ngā tai matatū: tides of Māori endurance, 2005)
"Nga Tai Matatu: Tides of Maori Endurance describes and analyses the position of the Maori people and Maori interests at the start of the third millennium. It also recognises the journeys from the past and makes projections into the future. The book builds on the highly successful Te Mana, Te Kawanatanga: The Politics of Maori Self-Determination but also introduces new issues and canvasses recent developments that have influenced Maori lives and Maori resources. Development is an ongoing process that has distant beginnings and no real ending. That sense of eternity is reflected in the Maori title; like the changing nature of the tide, Maori fortunes also change."–Book jacket.
Keywords: UNDRIP; crown policy; government relations; land tenure; law; mana motuhake; sovereignty; tino rangatiratanga; welfare policies

Chapter 8: Te Ngau o te Tai: The Sting of the Tide: Māori and the Law - Durie, Mason (Ngā tai matatū: tides of Māori endurance, 2005)
"Nga Tai Matatu: Tides of Maori Endurance describes and analyses the position of the Maori people and Maori interests at the start of the third millennium. It also recognises the journeys from the past and makes projections into the future. The book builds on the highly successful Te Mana, Te Kawanatanga: The Politics of Maori Self-Determination but also introduces new issues and canvasses recent developments that have influenced Maori lives and Maori resources. Development is an ongoing process that has distant beginnings and no real ending. That sense of eternity is reflected in the Maori title; like the changing nature of the tide, Maori fortunes also change."–Book jacket.
Keywords: government relations; law; mana motuhake; sovereignty; tino rangatiratanga; tiriti o waitangi/treaty of waitangi

Chapter 9: Rongotai: the Roar of the Ride: Māori in Parliament - Durie, Mason (Ngā tai matatū: tides of Māori endurance, 2005)
"Nga Tai Matatu: Tides of Maori Endurance describes and analyses the position of the Maori people and Maori interests at the start of the third millennium. It also recognises the journeys from the past and makes projections into the future. The book builds on the highly successful Te Mana, Te Kawanatanga: The Politics of Maori Self-Determination but also introduces new issues and canvasses recent developments that have influenced Maori lives and Maori resources. Development is an ongoing process that has distant beginnings and no real ending. That sense of eternity is reflected in the Maori title; like the changing nature of the tide, Maori fortunes also change."–Book jacket.
Keywords: government relations; kāwanatanga; law; mana motuhake; māori electorates; māori seats; parliament; self-determination; sovereignty; tino rangatiratanga

Empowering Indigenous Community Engagement and Approaches in Lake Restoration: An Aotearoa-New Zealand Perspective - Williams, Erica K.; Watene-Rawiri, Erina M.; Tipa, Gail T. (Lake Restoration Handbook: A New Zealand Perspective, 2018)
The Treaty of Waitangi forms the underlying foundation of the Crown–Māori relationship with regard to freshwater resources in Āotearoa-New Zealand. While there is no “one” Māori world view, there are principles and values that establish and reinforce whānau, hapū, rūnanga and iwi identity, and their responsibilities and rights to manage and use natural resources, including lakes. Lake restoration approaches that are grounded in tikanga Māori and Māori values and perspectives, and are co-designed to be responsive to the needs and aspirations of Māori, will ensure that outcomes are useful and of benefit to the participating indigenous community. The resulting outcomes are more likely to strengthen and add value to existing community initiatives, thus increasing efficiencies when capacity and capability across different expertise is in demand. This requires a commitment (by agencies and funders) to move beyond conventional understandings of who is “qualified” to engage in lake research and restoration initiatives. While hapū, rūnanga and iwi undoubtedly benefit from having their members qualify by being active participants in lake research and restoration efforts, in this chapter we emphasise the need for a more holistic approach that recognises and empowers whānau to engage as co-governors, co-leaders, researchers, as knowledge holders and as teachers. A truly collaborative lake restoration programme will provide multiple roles for Māori, including the development and implementation of monitoring and evaluation approaches.
Keywords: co-governance; environment; lake restoration; mātauranga māori; tikanga | indigenous law

A Genealogy of Indigenous Resistance - Hokowhitu, Brendan (Indigenous Identity and Resistance: Researching the Diversity of Knowledge, 2010)
Brings together the work of scholars working in Canada, New Zealand and the Pacific in an exploration of the multifaceted nature of indigenous studies and the concept of indigenous studies as an academic discipline. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: activism; ethnic identity; government; iwi taketake; land march; parliament; rangahau māori; resistance; tāngata whenua

Chapter 21: He Tātai Tuakiri: The ‘Imagined’ Criteria of Māori Identity - Leoni, Gianna; Wharerau, Marcelle; White, Tawini (Te kōparapara: an introduction to the Māori world, 2018)
Keywords: discrimination; history; identity; social conditions; social life and customs; stereotypes

Te Tiriti me Ōna Whakatau: The Waitangi Tribunal and Treaty Settlements - Ruru, Jacinta (Te kōparapara: an introduction to the Māori world, 2018)
Keywords: history; social conditions; social life and customs; tiriti o waitangi/treaty of waitangi; treaty settlements; tribunal reports; waitangi tribunal

Chapter 5: Kaitiakitanga: Land, People and Resource Management - Kawharu, Merata (Te kōparapara: an introduction to the Māori world, 2018)
Keywords: environment; history; kaitiakitanga; resource management; social conditions; social life and customs

Chapter 3: Whakapaparanga: Social Structure, Leadership and Whāngai - Kawharu, Merata; Newman, Erica (Te kōparapara: an introduction to the Māori world, 2018)
Keywords: hapū; hapū politics; history; iwi; rangatiratanga; social conditions; social life and customs; whanau

Chapter Five: Ka Pū Te Ruha, Ka Hao Te Rangatahi: Māori Identities in the Twenty-first Century - Kukutai, Tahu; Webber, Melinda (A land of milk and honey?: making sense of Aotearoa New Zealand, 2017)
"Since colonisation, New Zealand has been mythologised as a 'land of milk and honey' - a promised land of natural abundance and endless opportunity. In the twenty-first century, the country has become literally a land of milk and honey as agricultural exports from such commodities dominate the national economy. But does New Zealand live up to its promise? In this introductory textbook for first year sociology students, some of this country's leading social scientists help us to make sense of contemporary New Zealand. In 21 chapters, the authors examine New Zealand's political identity and constitution; our Māori, Pākehā, Pacific and Asian peoples; problems of class, poverty and inequality; gender and sexualities; and contemporary debates around ageing, incarceration and the environment. The authors find a complex society where thirty years of neoliberal economics and globalising politics have exacerbated inequalities that are differentially experienced by class, ethnicity, gender, sexuality and age. These social divides and problems are at the heart of this text. For sociology students and for a wider audience of New Zealanders, A Land of Milk and Honey? is a lively introduction to where we have come from, where we are now, and where New Zealand society might be headed"–Back cover.
Keywords: census; ethnic identity; identity; social change; social conditions; social life and customs

Chapter Two: Rangatiratanga, Kawanatanga and the Constitution - Walker, Ranginui (A land of milk and honey?: making sense of Aotearoa New Zealand, 2017)
"Since colonisation, New Zealand has been mythologised as a 'land of milk and honey' - a promised land of natural abundance and endless opportunity. In the twenty-first century, the country has become literally a land of milk and honey as agricultural exports from such commodities dominate the national economy. But does New Zealand live up to its promise? In this introductory textbook for first year sociology students, some of this country's leading social scientists help us to make sense of contemporary New Zealand. In 21 chapters, the authors examine New Zealand's political identity and constitution; our Māori, Pākehā, Pacific and Asian peoples; problems of class, poverty and inequality; gender and sexualities; and contemporary debates around ageing, incarceration and the environment. The authors find a complex society where thirty years of neoliberal economics and globalising politics have exacerbated inequalities that are differentially experienced by class, ethnicity, gender, sexuality and age. These social divides and problems are at the heart of this text. For sociology students and for a wider audience of New Zealanders, A Land of Milk and Honey? is a lively introduction to where we have come from, where we are now, and where New Zealand society might be headed"–Back cover.
Keywords: colonisation; he whakaputanga; kāwanatanga; kīngitanga; rangatiratanga; social change; social conditions; social life and customs; tiriti o waitangi/treaty of waitangi; treaty settlements

Introduction: Situating mixed race in New Zealand and the world - Webber, Melinda (Mana Tangatarua: mixed heritages, ethnic identity and biculturalism in Aotearoa/New Zealand, 2018)
"This volume explores mixed race/mixed ethnic identities in Aotearoa/New Zealand. Mixed race and mixed ethnic identity are growing in popularity as research topics around the world. This edited collection looks at mixed race and mixed ethnic identity in New Zealand: a unique context, as multiple ethnic identities have been officially recognised for more than 20 years. The book draws upon research across a range of disciplines, exploring historical and contemporary ways in which official and social understandings of mixed race and ethnicity have changed. It focuses on the interactions between race, ethnicity, national identity, indigeneity and culture, especially in terms of visibility and self-defined identity in the New Zealand context. Mana Tangatarua situates New Zealand in the existing international scholarship, positioning experiences from New Zealand within theoretical understandings of mixedness. The chapters develop wider theories of mixed race and mixed ethnic identity, at macro and micro levels, looking at the interconnections between the two. The volume as a whole reveals the diverse ways in which mixed race is experienced and understood, providing a key contribution to the theory and development of mixed race globally."–Provided by publisher.
Keywords: bicultural; ethnic identity; ethnicity; europeans; rangahau o te noho-ā-iwi; social conditions; te ao hurihuri; tikanga | indigenous law; tāngata whenua

The Foreshore and Seabed Act: Five years on, where to from here - Whare, Tracey (Māori and the environment: kaitiaki, 2010)
Keywords: citizenship; environment; environmental policy; kaitiakitanga; print only; social life and customs; taiao; water management

Doing Affect Around National Days: Mundane/Banal Practice or the Call of ‘Another Space’? - Mccreanor, Tim; Muriwai, Emerald; Wetherell, M.; Moewaka Barnes, H.; Moewaka Barnes, Angela (Everyday Nationhood: Theorising Culture, Identity and Belonging After Banal Nationalism, 2017)
The intense choreography of a nation’s identity is often exhibited through national days. In Aotearoa, New Zealand, national events such as Waitangi Day (6 February) and Anzac Day (25 April) provide affective public spaces that engage identity, belonging and inclusion while evoking dissent, reverence, unity and division. In this chapter, we analyse the choreography of affect and discourse related to Waitangi Day through media, observational video and focus group data. We explore affective–discursive positions related to Micheal Billig’s notion of banal nationalism, and expand on this through analysis of feelings, emotion, spirituality and the Māori concept, wairua. A social practice lens is used to study ways in which such affective labour contributes to a colonialist everyday nationalism. Findings offer important windows on how nationhood might be critiqued, challenged and diversified to more adequately represent the ongoing dynamics and tensions between Māori and Pākehā.
Keywords: Waitangi Day; memorialisation; memory; nationhood

Chapter 18: The Treaty of Waitangi and Recognition of Tikanga Māori - Mikaere, Ani (Waitangi Revisited, 2005)
Keywords: colonisation; government relations; history; land tenure; law; race relations; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi

Chapter 15: From the Sideline: Tikanga, Treaty Values and Te Papa - Tapsell, Paul (Waitangi Revisited, 2005)
Keywords: bicultural; government relations; history; land tenure; mana whenua; marae; museums; race relations; te papa museum; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty principles

The Wai 262 Claim: A Claim by Māori to Indigenous Flora and Fauna - Solomon, Maui (Waitangi Revisited, 2005)
Keywords: government relations; history; land tenure; race relations; tiriti o waitangi/treaty of waitangi; treaty claims; treaty settlements; waitangi tribunal

Chapter 10: Feast or Famine: Customary Fisheries Management in a Contemporary Tribal Society - Tuuta, Evelyn (Waitangi Revisited, 2005)
Keywords: crown policy; environment; government relations; history; kaitiakitanga; land tenure; māori rights; race relations; rangatiratanga; resource management; tiriti o waitangi/treaty of waitangi

Chapter 11: Recovering Fagin's Ill-Gotten Gains: Settling Ngāti Kahu's Treaty of Waitangi Claims Against the Crown - Mutu, Margaret (Waitangi Revisited, 2005)
Keywords: government relations; history; land tenure; race relations; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

Orakei - Kāwharu, Hugh (Waitangi Revisited, 2005)
Keywords: government relations; hapū; history; land tenure; ngāti whatua; political action; race relations; rangatiratanga; tiriti o waitangi/treaty of waitangi; tāngata whenua; waitangi tribunal

Chapter 6: Rangatiratanga and Social Policy - Kawharu, Merata (Waitangi Revisited, 2005)
Keywords: crown policy; education; government relations; hauora; health; history; land tenure; race relations; rangatiratanga; social policy; tiriti o waitangi/treaty of waitangi

Chapter 7: The Treaty of Waitangi and Social Well-being: Justice, Representation, and Participation - Sullivan, Ann (Waitangi Revisited, 2005)
Keywords: crown; elections; government relations; history; land tenure; local government; māori electorates; māori seats; parliament; race relations; social justice; tiriti o waitangi/treaty of waitangi; treaty principles; voting

Chapter 1: Tino Rangatiratanga - Durie, Mason (Waitangi Revisited, 2005)
Keywords: constitution; government relations; history; kotahitanga; land tenure; marae; nationhood; race relations; self-governance; tiriti o waitangi/treaty of waitangi

Chapter Thirteen: New Māori Politics 1990s-2000s - Bargh, Maria (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"–Publisher's information.
Keywords: elections; government relations; history; iwi; iwi chairs forum; kāwanatanga; mana party; māori electorates; māori seats; social conditions; te pāti māori; tikanga | indigenous law; tāngata whenua; voting

Māori Urban Protest Movements - Taonui, Rawiri (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"–Publisher's information.
Keywords: discrimination; foreshore and seabed act 2004; government relations; hikoi ki waitangi; history; kaitiakitanga; land march; māori womens welfare league; nga tamatoa; parihaka; poverty; protest; racism; rangatiratanga; resistance; social conditions; springbok tour protests; takaparawhau bastion point; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; tāngata whenua; urbanisation

Constitutional Transformation - Mulholland, Malcolm; Tawhai, Veronica (Weeping Waters: The Treaty of Waitangi and Constitutional Change, 2017)
"Weeping Waters is a must read for anyone who wants to be informed about the current debate regarding the Treaty of Waitangi and a constitution for Aotearoa New Zealand. The book features essays from eighteen well-known and respected Maori figures including Professor Margaret Mutu, Bishop Muru Walters, Judge Caren Fox and lawyer Moana Jackson. This is the first book in recent years to offer a Maori opinion on the subject of constitutional change. It shows how Maori views have been ignored by successive governments and the courts and how Maori have attempted to address constitutional issues in the past. The book also provides suggestions for a pathway forward if the Treaty of Waitangi is to be fully acknowledged as the foundation for a constitution for Aotearoa New Zealand."–Publisher.
Keywords: constitution; crown law; tiriti o waitangi/treaty of waitangi

Chapter 5: Where to next? Decolonisation and the stories in the land: Imagining Decolonisation - Jackson, Moana (Imagining Decolonisation, 2020)
Keywords: colonisation; decolonisation; hapū politics; iwi politics; rangatiritanga; tikanga | indigenous law

Colonization as myth-making - Jackson, Moana (Being indigenous: perspectives on activism, culture, language and identity, 2019)
Keywords: colonisation; crown; ethnic identity; government; land loss; land theft; political power; rangatiratanga; tiriti o waitangi/treaty of waitangi

Enhancing Indigenous Peoples' Participation at the United Nations - Charters, Claire (International Work Group of Indigenous Affairs, 2017)
Keywords: not sure if maori

Comparative Constitutional Law and Indigenous Peoples: Canada, New Zealand and the USA - Claire Charters (Comparative Constitutional Law, 2011)
Keywords: constitution; crown law; crown policy; kāwanatanga; voting

Indigenous legal theory: some initial consideration - Benjamin J. Richardson; Charters, Claire (Indigenous peoples and the law: comparative and critical perspectives, 2009)
"Provides an historical, comparative and contextual analysis of various legal and policy issues affecting indigenous peoples. It focuses on the common law jurisdictions of Australia, Canada, New Zealand and the United States, as well as relevant international law developments"–Back cover.
Keywords: crown law; ethnic identity; international law; iwi taketake; law; print only; self-determination

Kāwanatanga, Tino Rangatiratanga and the Constitution - Walker, Ranginui; McIntosh, Tracey (New Zealand and the World, 2017)
Keywords: constitution; kāwanatanga; tino rangatiratanga

Chapter 1: Reclaiming Māori education - Walker, Ranginui (Decolonisation in Aotearoa: Education, research and practice, 2016)
Keywords: assimilation; colonisation; education

Tribal data sovereignty: Whakatōhea rights and interests - Maui Hudson; Dickie Farrar; Lesley McLean (Indigenous Data Sovereignty, 2016)
The vast array of activities that tribal organisations in Aotearoa/New Zealand are responsible for illustrates the importance of high-quality information to support their decision-making. Tribal information needs encompass a broad range of domains, types of information and processes for management. This chapter examines the growingiwi(tribal) interest in data and their uses in the context of oneiwi, Te Whakatōhea, to explore howiwiare beginning to conceptualise their rights and interests over data in Aotearoa/New Zealand. It is focused on the Whakatōhea Māori Trust Board and how it is collecting and becoming the steward for a range of
Keywords: data sovereignty; iwi sovereignty; tino rangatiratanga

Chapter Five – Māori Representation and Participation in National and Local Government Politics - Sullivan, Ann (Indigenous politics: institutions, representation, mobilisation, 2015)
Keywords: ethnic identity; ethnicity; government; government relations; iwi taketake; māori electorates; māori seats; tiriti o waitangi/treaty of waitangi; treaty obligations

The Humpty Dumpty Principle at work: The role of mistranslation in the British Settlement of Aotearoa. 'The Declaration of Independence' and 'He Whakaputanga o te Rangatiratanga o nga hapu o Nu Tireni' - Mutu, Margaret (For better or worse: translation as a tool for change in the South Pacific, 2014)
Keywords: colonisation; he whakaputanga; oceania

Chapter Four: The Treaty of Waitangi in the Postcolonial Era - Walker, Ranginui (Waitangi Revisited, 2005)
Keywords: colonisation; government relations; history; land march; land tenure; post-colonialism; race relations; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

Chapter Seventeen: 'As for these blankets, burn them' Māori and Indigeneity - Hokowhitu, Brendan (Huia histories of Māori: ngā Tāhuhu Kōrero, 2012)
"Collection of 17 essays from Māori scholars which cover customary law, ancestral law, the natural world, Māori urban protest, health, politics, and customary language and expression"–Publisher's information.
Keywords: government relations; history; identity; indigenous rights; pan-indigenous movement; social conditions; tikanga | indigenous law; tāngata whenua

Unravelling colonial weaving - Mutu, Margaret (Stroppy old women: 52 Kiwi women, who've been around long enough to know, tell you what's wrong with the world, 2015)
What do ... Judith Ablett-Kerr, Pinky Agnew, Donna Akersten, Judith Baragwanath, Janet Beech, Carole Beu, Rob Broughton, Judy Callingham, Trish Costigan, Valerie Davies, Lindsey Dawson, Eve de Castro-Robinson, Debbie Dorday, Dorothy Dudek Vinicombe, Anne Else, Jacquie Fahey, Peggy Fairbairn-Dunlop, Chris Fletcher, Tui Flower, Emerald Gilmour, Tina Grenville, Ruth Harley, Rosie Horton, Glenda Hughes, Sue Kedgley, Jan Kemp, Anne Kennedy, Shona Laing, Helen Leach, Vinka Lucas, Sue McCauley, Elizabeth McRae, Marama Martin, Margaret Mutu, Frances Pitsilis, Ruth Pretty, Wendy Pye, Jenny Rankine, Cecilie Rushton, Catherine Saunders, Karen Soich, Pieter Stewart, Anne Thorp, Mary-Jane Tomasi, Jools Toppp, Jodi Vaughan, Prue Wallis, Ans Westra, Reina Whaitiri, Dale Williams, Margaret Wilson and Alice Worsley ... have in common? They're all irate about something, sounding off on topics from ageing to architecture, shop assistants to short skirts, tablecloths to technology, and many more, in the female follow-up to the popular Grumpy Old Men books. These strops are even more controversial, hard-hitting and funny than the male versions. This is the perfect gift for stroppy old women of all ages.
Keywords: wāhine māori

Mana Maori motuhake Maori concepts and practices of sovereignty - Mutu, Margaret (Routledge handbook of critical indigenous studies, 2021)
Keywords: colonisation; ethnicity; he whakaputanga; mana motuhake; rangatiratanga

The "false generosity" of treaty settlements: innovation and contortion - Te Aho, Linda (International Indigenous Rights in Aotearoa New Zealand, 2017)
In Aotearoa New Zealand the ways in which indigenous claims to lands and waters are addressed are often looked to as good, or even best, practice by indigenous peoples around the world. While things are far from perfect, in recent decades Maori have succeeded in changing perceptions about the Treaty of Waitangi as the foundation of the nation, and work steadily continues on settling outstanding Treaty claims. The resulting Treaty of Waitangi settlements are negotiated arrangements which aim to remove a sense of historical grievance and achieve significant rebuilding of the Maori economy. They are seen by some as dynamic and powerful steps towards economic independence, as a means of recognising special relationships to lands and waters, and a necessary prerequisite to improved relationships between the state and the indigenous Maori in the future. ¹ Critics see the settlements and the processes followed to reach them as too heavily weighted in the government's favour. ² They argue that the settlements do not sufficiently compensate for actual losses. They are said to pit Maori against Maori. Diverse claimant groups are effectively forced to negotiate within standardised and fixed parameters. For these and other reasons, the settlement agreements, policies and processes have been labelled as divisive and compromising self-determination. ³
Keywords: tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

Māori wards and advisory boards - Bargh, Maria (Local Government in New Zealand: Challenges & Choices, 2016)
Local government in New Zealand faces major challenges. Among the most pressing are continual legislative change, threats to its autonomy, the gradual erosion of community voices in council planning and decision-making, and the need for funding solutions to ensure property rates remain affordable. As well, there is an urgent need for a more coordinated approach across central government on major policy issues such as climate change and housing. This book exposes these challenges and proposes and debates solutions for the future of our local government. Strong local government is vital for ensuring economic growth across and within regions and local communities, for enhancing community wellbeing, for funding and providing the infrastructure needed for, in some cases, rapidly growing and diverse communities, for ensuring our environment is valued and protected, and for planning for development in a time of constraint on resources. This book is a 'one-stop information shop' on local government that can be used by those who regularly interact with or study this area of government, by those working within local authorities, and by those who actively work to ensure their communities grow in a sustainable way.
Keywords: local government

The Māori seats - Bargh, Maria (New Zealand Government and Politics, 2015)
Keywords: Elections – New Zealand; Financial crises – New Zealand; Global Financial Crisis; 2008-2009; Māori (New Zealand people) – Politics and government; Nationalism – New Zealand; New Zealand – Foreign relations; New Zealand – Politics and government; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

Unearthing (de)colonial legal relations: Mining law in Aotearoa New Zealand - Bargh, Maria; Wagner, Estair Van (Decolonizing law: Indigenous, third world and settler perspectives, 2021)
Keywords: colonisation; crown policy; decolonisation; environment; tiriti o waitangi/treaty of waitangi

Māori resource management innovations - Bargh, Maria (Routledge Handbook of Critical Indigenous Studies, 2020)
The historical context of colonial legacies and capitalist policies are shaping responses to climate change but so too are non-capitalist and alternative-capitalist practices. Indigenous peoples’ world-views are commonly argued to align with non-capitalist approaches and often said to be the answer to climate change. However, Indigenous peoples are never only ‘ecological natives’ ‘living at one with nature’ but have multiple roles and identities in the political economy. Indigenous world-views could be used in ways to support capitalist practices and policies (which many argue have caused climate change) or to support alternative-capitalist practices (which others argue promote harmonious relationships between humans and the planet).
Keywords: capitalism; climate change; environment

Māori Interests and Rights: Four Sites at the Frontier - Bargh, Maria; Jones, Carwyn (Public Policy and Governance Frontiers in New Zealand, 2020)
Keywords: crown policy; government; iwi politics; kaitiakitanga; kāwanatanga; māori rights; rangatiratanga

Chapter 40: Indigenous finance: treaty settlement finance in Aotearoa New Zealand - Bargh, Maria (The handbook of diverse economies, 2020)
"Theorising and illustrating diverse, more-than-capitalist economies, this broad-ranging Handbook presents ways in which it is possible to imagine and enact other ways of being. It gathers together empirical examples of diverse economic practices and experiments from across the world, framed by in-depth discussions of key theoretical concepts. Organised into thematic sections, the Handbook moves from looking at diverse forms of enterprise, to labour, transactions, property, and finance as well as decentred subjectivity and diverse economies methodology. Chapters present a wide diversity of economic practices that make up contemporary economies, many of which are ignored or devalued by mainstream economic theory. Pushing the boundaries of economic thinking to include more than human labour and human/non-human interdependence, it highlights the challenges of enacting ethical economies in the face of dominant ways of thinking and being. Economic geography, political economy and development studies scholars will greatly appreciate the empirical examples of diverse economic practices blended with theory throughout the Handbook. It will also benefit policy-makers and practitioners working within diverse economies, or looking to create more ethical ways of living"– Provided by publisher.
Keywords: colonisation; economic aspects; governance; land loss; land ownership; tiriti o waitangi/treaty of waitangi; treaty settlements

A Tika Transition - Bargh, Maria (A Careful Revolution Towards a Low-emissions Future, 2019)
Climate crisis is upon us. By choice or necessity, New Zealand will transition to a low-emissions future. But can this revolution be careful? Can it be attentive to the disruptions it inevitably creates? Or will carefulness simply delay and dilute the changes that future people require of us? This timely collection brings together eleven authors to explore the politics and practicalities of the low-emissions transition, touching on issues of justice, tikanga, trade-offs, finance, futurism, adaptation, and more.
Keywords: climate change; economic aspects; environmental management

Ngā Whai Take: Reframing Indigenous Development - Ruwhiu, Diane; Amoamo, Maria; Carter, Lynette; Bargh, Maria; Ruckstuhl, Katharina; Carr, Anna; Awatere, Shaun (The Routledge Handbook of Indigenous Development, 2022)
This chapter explores how Maori developmental aspirations require a multidimensional view of economy linked to Maori identity, landscape and worldview. It aims to reframe the Maori, and, by extension, wider concepts of Indigenous economy to one that has meaning to Maori communities, and thus more holistically appreciates the true notion of ‘value’. The chapter presents Maori business case studies that illustrate distinctive elements of connection between Maori worldview, forms of organization and economy. It offers insight into how we might realize meaningful development for Indigenous communities more broadly. Non-economic variables such as relationships, reciprocity and connection are privileged, and matauranga Maori, identity, tikanga Maori, whanaungatanga, whakapapa, and manaakitanga guide Maori business structure, governance and practice. Whai take represents a broader conceptualization of Maori economy that more meaningfully engages the multifaceted nature of Maori socio-economic activity.
Keywords: economic development; rangatiritanga; te ao Māori; whanaungatanga

Māori Development and Neoliberalism - Bargh, Maria (Resistance: an Indigenous response to neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: development; history; neoliberalism; political Ideologies; protest

Rights and Sovereignty of Indigenous Peoples: Implications for Foreign Policy - Bargh, Maria (Public Participation in Foreign Policy, 2012)
The predominant forms of foreign policy discussed these days are underpinned by an assumption of Crown sovereignty in Aotearoa New Zealand. However, the first diplomatic relations and foreign policy in this country were conducted by hapū and iwi Māori.1 Prior to the 1800s, Māori had a long history of interaction in the Pacific and with other nations. Such interactions were governed by specific legal and political practices and institutions. A number of the concepts upon which these practices and institutions were based included whakapapa (genealogy), utu (balance), mana (respect) and koha (reciprocity).2
Keywords: diplomacy; foreign policy; free trade agreement; hapū politics; human rights; international relations; iwi politics; te ao Māori

From new paternalism to new imaginings of possibilities in Australia, Canada and Aotearoa/New Zealand: Indigenous rights and recognition and the state in the neoliberal age - Bargh, Maria; Howard-Wagner, Deirdre; Altamirano-Jimenez, Isabel (The Neoliberal State, Recognition and Indigenous Rights, 2018)
The election of Evo Morales as the first indigenous President of Bolivia in 2005 is widely credited to the Cochamba Water War (Spronk 2007: 8). The Cochamba Water War progressed from an indigenous movement and a specific issue to the creation of an indigenous political party and election of the first indigenous President. The Bolivian water war, the Puebla Panama Plan in Mexico, the Mackenzie Valley pipeline in Canada (Altamirano‐Jiménez 2004) and Māori resistance to the neoliberal agenda from 1984 onwards (Bargh 2007: 26) inspired much theorising about indigenous people successfully contesting neoliberalism (AltamiranoJiménez 2004, Bargh 2007, Spronk 2007: 8, Postero 2007). Bargh and others, for example, documented not only ‘overt Māori resistance to neoliberal policies, but also more subtle stories of activities, which The neoliberal state, recognition and indigenous rights implicitly challenge neoliberal practices and assumptions by their support for other ways of living’ (Bargh 2007: 1). Scholars make visible the persistence of the colonial in the concrete and material conditions of everyday neoliberal governance and life (Howard-Wagner & Kelly 2011: 103). As Bargh (2007), Altamirano-Jiménez (2013), Howard-Wagner (2010b, 2015) and others note, indigenous categorisations of neoliberal practices as a form of colonisation relate to a concern that neoliberalism in its multiple forms poses a threat to indigenous ways of life. This scholarship also critically reflects on the reshaping of the relationship between the state and indigenous peoples under neoliberalism (Altamirano-Jiménez 2004, Bargh 2007, Howard-Wagner 2009). For example, it draws attention to the increasing intervention in the lives of indigenous peoples (Howard-Wagner 2007, 2009, 2010a, 2010b) and the dispossession of indigenous people through privatisation (Wolfe 2006, Howard-Wagner 2012, Altamirano-Jiménez 2013, Coulthard 2014). It does not, however, preclude agency, resistance and decolonisation. Interpretive micro-studies about indigenous peoples’ engagement with neoliberalism provide particular value. They tell us about actually existing neoliberalism in the context of intervention in the everyday lives of indigenous peoples, contests over rights, contests over policy and the complex decisions indigenous people are making about how to protect their rights and navigate diverse economies involving neoliberal policies and practices.
Keywords: crown policy; neoliberalism; treaty obligations; waitangi tribunal; water management; water rights

Māori and the 2017 General election: party, participation, and populism - Greaves, Lara; Hayward, Janine (A Populist Exception? The 2017 New Zealand General Election, 2020)
Keywords: elections; kāwanatanga; māori electorates; māori seats; political participation; political parties; te pāti māori; voter turnout

How the Māori Party defied expectations at the 2020 election - Greaves, Lara; Morgan, Ella (Politics in a pandemic : Jacinda Ardern and New Zealand's 2020 election, 2021)
Keywords: covid-19

The politics of reconciliation in Australia and New Zealand - O’Sullivan, Dominic (Injustice, Memory and Faith in Human Rights, 2017)
This chapter draws on New Zealand examples to contextualize its assessment of reconciliation as public memory in Australian policy discourse. The Treaty of Waitangi has provided the rationale and framework for successive New Zealand governments to say sorry for acts of aggression against Maori tribes. In New Zealand, sorrow is expressed through Acts of Parliament that serve not only as instruments of restitution but as symbols of public memory. Faith and memory are similarly important to wider Christian treaty discourses, as it was Anglican missionaries who drafted the agreement and translated it from English to Maori. The Pastoral letter is drawn into Catholic public memory to justify the development of a public theology of reconciliation. Self-determination belongs first and foremost to individuals, but in Catholic teaching the human person is fundamentally social and exercises the rights and responsibilities of their human being in association with others.
Keywords: reconciliation; religion

Indigenous Māori knowledge and perspectives of ecosystems - Harmsworth, Garth R; Awatere, Shaun (Ecosystem services in New Zealand : conditions and trends, 2013)
A framework/model based on Māori knowledge, values and perspectives is presented that distinguishes ‘cultural values’ from ‘cultural services’ and extends the deﬁnition of cultural values across the whole ecosystem services framework. Māori aspirations and well-being are interdependent on ecosystems and ecosystem services. Ultimately Māori wish to use these ecosystem approaches and frameworks to increase participation and inclusion in decision-making, to achieve multidimensional aspirational goals and desired indigenous outcomes.
Keywords: decision making; environment; environmental management; planning; policy making

Maori self-determination and a liberal theory of indigeneity - O'Sullivan, Dominic (Restoring Indigenous Self-Determination: Theoretical and Practical Approaches, 2014)
Indigenous peoples find themselves locked in power struggles with states and transnational actors who resist their claims, raising important questions in theory and practice. Edited by Marc Woons.
Keywords: rangatiratanga; self-determination; sovereignty

Reflections from an Indigenous Community on Volcanic Event Management, Communications and Resilience - Gabrielsen, H.; Procter, J.; Rainforth, H.; Black, T.; Harmsworth, G.; Pardo, N. (Observing the Volcano World: Volcano Crisis Communication, 2018)
Ngāti Rangi, an indigenous tribe of Aotearoa New Zealand, live on the southern flanks of their ancestral mountain, Ruapehu, an active volcano. Ruapehu has erupted and caused lahars within living memory, and nearby Tongariro erupted as recently as 2012. Ngāti Rangi and other tribes affiliated to these mountains are intimately connected to and familiar with the moods, signs, and language of the mountains and have valuable knowledge to contribute to decision-making and warning systems during volcanic events. To date this knowledge or mātauranga Māori has been somewhat under-utilised, and Ngāti Rangi have not always been included in decision-making processes during volcanic events. But communication is improving, and Ngāti Rangi have begun a journey of building their own monitoring, information collection, and communication systems. Past and present monitoring, warning systems, communications and tribal civil defence resources are examined to determine how Ngāti Rangi and their tribal knowledge can be better recognised, communications with governmental volcanic hazard management agencies improved to ultimately work together to improve outcomes for the tribe and local community.
Keywords: environment; event management; mātauranga māori; natural disaster; response strategy; risk management

Chapter Six: Māori and Freshwater Law - Ruru, Jacinta (Future challenges for Māori: he kōrero anamata, 2013)
"This collection of essays by 22 contributors, experts in their fields, represents the accumulated knowledge of a group of Māori scholars on a variety of contemporary issues, including Māori identity and self-determination, the environment, te reo Māori, education, social and economic issues, and governance and leadership. The collection is a result of a series of seminars organised by the MANU AO Academy, which is a national inter-university Māori Academy for academic and professional advancement"–Publisher information.
Keywords: government; mana motuhake; rangatiratanga; social conditions; sovereignty

Indigenous Identities and the Politics of Authenticity - Harris, Michelle; Carlson, Bronwyn; Poata-Smith, Evan (The Politics of Identity, 2013)
The very question of Indigenous authenticity, as Jeffrey Sissons reminds us, “…has deep roots within colonial racism” (2005, 43). Racialisation and the practice of creating and imbuing racial categories with seemingly impermeable boundaries and indestructible meanings has, after all, underpinned a range of colonial practices from the systematic alienation of Indigenous land and resources to child abduction. Regimes of biological and cultural authenticity continue to shape state policies and practices that regulate the everyday lives of Indigenous people around the world. Indeed, in some contexts, expectations of Indigenous cultural purity or environmental naturalness exist alongside the imposition of varying degrees
Keywords: crown policy; identity; racism

Emergent Identities: The Changing Contours of Indigenous Identities in Aotearoa/New Zealand - Poata-Smith, E.S Te Ahu (The Politics of Identity, 2013)
Keywords: ethnic identity; identity

Maori identities; fixed, forced, and fluid - McIntosh, Tracey (New Zealand identities: departures and destinations, 2005)
Social scientists attached to the Centre for Applied Cross Cultural Research at Victoria University of Wellington examine issues of New Zealand identity.
Keywords: ethnic identity; ethnicity; identity

Māori and Prison - McIntosh, Tracey; Workman, Kim (The Palgrave Handbook of Australian and New Zealand Criminology, Crime and Justice, 2017)
Keywords: crown policy; incarceration; racism; systematic racism

Indigenous Rights, Poetry and Decarceration - McIntosh, Tracey (Human Rights and Incarceration, 2018)
Keywords: incarceration; indigenous soveriegnty; mana motuhake; māori rights; rangatiratanga

Prison Abolitionism: Philosophies, Principles and Practices - Lamusse, Ti; McIntosh, Tracey (The Aotearoa Handbook of Criminology, 2021)
No description supplied
Keywords: criminal justice system; crown policy; discrimination; law; prison abolition; rangatiratanga; tikanga | indigenous law; whanau

Women, incarceration and settler colonial control - McIntosh, Tracey (Women, Crime and Justice in Context: Contemporary Perspectives in Feminist Criminology from Australia and New Zealand, 2022)
This chapter examines settler colonial crime control and its impacts on Indigenous women. High rates of victimisation and high levels of over-policing and over-incarceration mark Indigenous people’s experience of settler colonialism. This chapter explores the historical and contemporary conditions of colonialism through a gender lens, exploring in particular the impact of prison on Indigenous women’s lives. The chapter is based on an interview with and subsequent written notes by Professor McIntosh in 2020 discussing women, incarceration and settler colonial control in the Aotearoa New Zealand setting.
Keywords: criminalisation; crown policy; crown violence; incarceration; prison; racism; wāhine māori

Settler violence, family, and whānau violence in Aotearoa New Zealand - McIntosh, Tracey (Women, Crime and Justice in Context: Contemporary Perspectives in Feminist Criminology from Australia and New Zealand, 2022)
This chapter looks at the impact on M?ori that colonial and neo-colonial practices of dispossession and immiseration have had on elevated family violence rates in Aotearoa New Zealand. In reflecting on interpersonal violence, it seeks to locate systemic forms of violence, such as legislative violence, institutional violence, and economic violence, and their relationship with family violence. It draws on David Nixon’s (2011) notion of slow violence to look at the intergenerational harm of poverty, racism, and entrenched negative social issues. The focus then moves to Indigenous solutions to family violence that demonstrate the power of lived experience and social and cultural expertise to support healing and transformation in M?ori communities.
Keywords: crown policy; crown violence; dispossession; family violence; intergenerational trauma; land loss

Māori Perspectives on Conscious Capitalism - Dell, Kiri; Houkamau, Carla; Mika, Jason; Newth, Jamie (The Spirit of Conscious Capitalism: Contributions of World Religions and Spiritualities, 2022)
Māori, the Indigenous peoples of Aotearoa New Zealand, were formerly colonised by the British from 1840 following the signing of te Tiriti o Waitangi (the Treaty of Waitangi). Māori remain numerically significant in New Zealand and are the second largest ethnic group after Pākehā (New Zealand Europeans). Pre-colonial, traditional Māori society, through collective economic practice, was balanced to protect whakapapa (geological relationships) and natural resources. This balance was key to survival, and cultural practices evolved to maintain this balance. Despite the ongoing impacts of colonisation since the 1800s, Māori have maintained strong cultural values, which manifest in contemporary approaches to business that strive to balance the interests of future and past generations based on a spiritual connection to the natural world. Conscious capitalism, as envisioned by Mackey and Sisodia (2014), describes higher-order principles that align with Māori approaches to business, but their limitation is articulating the role of spirituality in entrepreneurial activity. This chapter extends Mackey and Sisodia’s higher-order tenets drawing on Māori values, primarily, mana (a supernatural force for status in a person, place, or object) and hau (the practice of reciprocal relations) to articulate how spiritual and cultural values shape contemporary Māori business endeavours. To illustrate, we offer a case study of a Māori business, led by one of the authors, which is grappling with tensions between cultural and commercial imperatives.
Keywords: capitalism; mana party; unsure if politics

Letty Brown, Wahine Toa - Harris, Aroha (Shifting Centres: Women and migration in New Zealand history, 2002)
History of Lettty Brown, advocate and member of groups such as the Womens Welfare League during urbanisation 1950s-1906s
Keywords: mana wāhine; urbanisation

Maori and ‘the Maori Affairs’ - Harris, Aroha (Past Judgement: Social Policy in New Zealand History, 2004)
Keywords: crown policy; history; kāwanatanga; māori affairs; social policy; welfare policy

"Assaulting the Ears of Government": The Indian Homemakers' Clubs and the Maori Women's Welfare League in Their Formative Years - Harris, Aroha (Indigenous Women and Work: From Labor to Activism, 2012)
Keywords: history; mana wāhine; native americans

The Politics of Power in Indigenous Oral History - Mahuika, Nepia (Rethinking Oral History and Tradition: An Indigenous Perspective, 2019)
"For many indigenous peoples, oral history is a living intergenerational phenomenon that is crucial to the transmission of our languages, cultural knowledge, politics, and identities. Indigenous oral histories are not merely traditions, myths, chants or superstitions, but are valid historical accounts passed on vocally in various forms, forums, and practices. Rethinking Oral History and Tradition: An Indigenous Perspective provides a specific native and tribal account of the meaning, form, politics and practice of oral history. It is a rethinking and critique of the popular and powerful ideas that now populate and define the fields of oral history and tradition, which have in the process displaced indigenous perspectives. This book, drawing on indigenous voices, explores the overlaps and differences between the studies of oral history and oral tradition, and urges scholars in both disciplines to revisit the way their fields think about orality, oral history methods, transmission, narrative, power, ethics, oral history theories and politics. Indigenous knowledge and experience holds important contributions that have the potential to expand and develop robust academic thinking in the study of both oral history and tradition.–
Keywords: historiography; history; oral history; tikanga | indigenous law

Maori Disputes and Their Resolution - Quince, Khylee (Dispute resolution in New Zealand, 2007)
http://librarysearch.auckland.ac.nz/primo_library/libweb/action/display.do?fn=search&doc=uoa_voyager1760462&vid=UOA2_A
Keywords: crown law; rangatiratanga; tikanga | indigenous law

Pandemic Paternalism: A Reflection on Indigenous Data from Aotearoa - Kukutai, Tahu; Cormack, Donna (COVID 19 FROM THE MARGINS: PANDEMIC INVISIBILITIES, POLICIES AND RESISTANCE IN THE DATAFIED SOCIETY, 2021)
Keywords: covid-19

The Structure of Urban Māori Identities - Kukutai, Tahu (Indigenous in the City: Contemporary Identities and Cultural Innovation, 2013)
Research on Indigenous issues rarely focuses on life in major metropolitan centres. Instead, there is a tendency to frame rural locations as emblematic of authentic or "real" Indigeneity. While such a perspective may support Indigenous struggles for territory and recognition, it fails to account for large swaths of contemporary Indigenous realities, including the increased presence of Indigenous people in cities. The contributors to this volume explore the implications of urbanization on the production of distinctive Indigenous identities in Canada, the US, New Zealand, and Australia. In doing so, they demonstrate the resilience, creativity, and complexity of the urban Indigenous presence.
Keywords: identity; urbanisation

Chapter 9: Indigenous Data Sovereignty: Implications for Data Journalism - Kukutai, Tahu; Walter, Maggie (The Data Journalism Handbook: Towards a Critical Data Practice, 2021)
Keywords: indigenous data sovereignty

Chapter 21: Indigenous Data Sovereignty - Kukutai, Tahu (The State of Open Data; Histories and horizons, 2019)
Keywords: data; data sovereignty; iwi governance; open data

Indigenous Peoples, Data, and the Coloniality of Surveillance - Cormack, Donna; Kukutai, Tahu (New Perspectives in Critical Data Studies: The Ambivalences of Data Power, 2022)
In Aotearoa New Zealand (Aotearoa NZ), Māori (the Indigenous peoples of New Zealand) have long been objects of surveillance by state institutions and agents. State representations have centred on constructions of difference and deviance, on understandings of Indigenous peoples as dangerous, and on the management of Indigenous resistance to colonialism. This chapter considers how contemporary state surveillance practices in Aotearoa NZ, enabled by the expanded use of big data and linked government datasets, function to regulate and manage Māori. Through this lens, we explore continuities of current data practices for Indigenous peoples with the racialised logics and social orders set in place as part of global systems of imperialism and colonialism. Recognising that resistance has always been a part of Indigenous responses to colonialism, we also explore how Māori Data Sovereignty (MDSov), as part of broader Indigenous Data Sovereignty (IDS) movements globally, provides opportunities to counter and disrupt prevailing data relations and to imagine alternative futures.
Keywords: colonisation; data; data sovereignty; indigenous data sovereignty; surveillance

Beyond the “Abyssal Line”: Knowledge, Power, and Justice in a Datafied World - Cormack, Donna; King, Paula (The Oxford Handbook of Indigenous Sociology, 2021)
Colonization fundamentally disrupted Indigenous knowledge systems, establishing epistemic hierarchies that privilege Eurocentric colonial epistemologies and methodologies. In this chapter, the authors explore how epistemic hierarchies are (re)produced in the current context of “big data” and datafication, in particular for mokopuna Māori in the nation-state known as New Zealand (NZ). (We use the concept of “mokopuna Māori” to refer to and position Māori babies, children, and young people within the Māori world as the sacred reflection of our ancestors and a blueprint for future generations.) The chapter then considers the possibilities for Indigenous epistemic justice in the “zone of nonbeing” or beyond the “abyssal line.”
Keywords: colonial methodology; colonisation; data; data sovereignty; heirarchy; kaupapa māori; methodology

Mining law in Aotearoa New Zealand - Wagner, Estair Van; Bargh, Maria (Decolonizing Law, 2021)
Minerals in Aotearoa New Zealand are regulated by the Crown Minerals Act, 1991 (the CMA). Like other statutes in New Zealand, the CMA recognizes Te Tiriti o Waitangi (the Treaty of Waitangi), signed by the British and Māori in 1840, and therefore the relationship between Māori and the lands and resources governed by the Act. The Treaty relationship continues to play a crucial role in conflicts about land and resources and is central to the practice of decolonization for Māori. However, as we argue, the governance of relationships between people and minerals, as foundational elements of material systems, extend much further to the Māori legal orders developed throughout Aotearoa.

Chapter 2: "Publishing the Space": Data sovereignty and self-determination in Aotearoa New Zealand - Kukutai, Tahu; Cormack, Donna (Indigenous Data Sovereignty and Policy, 2020)
This book examines how Indigenous Peoples around the world are demanding greater data sovereignty, and challenging the ways in which governments have historically used Indigenous data to develop policies and programs. In the digital age, governments are increasingly dependent on data and data analytics to inform their policies and decision-making. However, Indigenous Peoples have often been the unwilling targets of policy interventions and have had little say over the collection, use and application of data about them, their lands and cultures. At the heart of Indigenous Peoples’ demands for change are the enduring aspirations of self-determination over their institutions, resources, knowledge and information systems. With contributors from Australia, Aotearoa New Zealand, North and South America and Europe, this book offers a rich account of the potential for Indigenous data sovereignty to support human flourishing and to protect against the ever-growing threats of data-related risks and harms.
Keywords: colonisation; data sovereignty; policy; self-determination

How the Māori Party defied expectations at the 2020 election - Morgan, Ella; Greaves, Lara (Politics in a pandemic: Jacinda Ardern and New Zealand's 2020 election, 2021)
Is this the springboard for a bigger resurgence in 2023?
Keywords: elections; electorates; labour party; parliament